Differential Immunoexpression of BRAF/V600E, Senescence Markers, PTEN, and T-type Calcium Channels in Acquired Naevi According to their Histopathological and Dermoscopic Classification - Sara Moreno; Oscar Maiques; Carla Barcelo; Marta Romero; Maria Santacana; Ignacio Gómez; Dolors Cuevas; Ana Velasco; Alvar Vea; Anna Macia; Ramon Boix; Joan Valls; et al. (Medical Journals Sweden, 2021)
BRAF/V600E mutation and other cell growth/growth-control mechanisms are involved in naevogenesis and melanomagenesis. Immunoexpression of BRAF/V600E and other molecules (p16, phosphatase and tensin homologue (PTEN), Ki67, hTERT and Cav3.1 and 3.2 calcium channels) were investigated in 80 histopathologically and dermoscopically classified acquired naevi. Regarding BRAF/V600E, dysplastic naevi showed lower immunostaining than common naevi, which was significant in comparison with intradermal naevi, which showed the highest BRAF/V600E histoscore. Junctional naevi showed the lowest BRAF/V600E levels. Globular/cobblestone and reticular dermoscopic patterns were consistently associated with high and low BRAF/V600E immunoexpression, respectively, but Zalaudek's peripheral globule pattern (CR/PG) showed the highest BRAF/V600E immunoexpression. Among global patterns, the previously not investigated multicomponent pattern showed the lowest BRAF/V600E immunoexpression. Regarding the remaining biomarkers, new immunohistochemical features were found, in particular p16 and PTEN low expression in multicomponent pattern; and Ki67, hTERT and Cav.3.1 high expression in CR/PG. In conclusion, histopathology and dermoscopy provide complementary information regarding the biology of melanocytic naevi.